Comparing the effects of tramadol and fentanyl on anxiety and postoperaıve pain in impacted third molar surgery [Gömülü üçüncü molar diş cerrahisinde tramadol ve fentanilin anksiyete ve postoperatif aǧrı üzerine etkilerinin karşılaştırılması] - (:unkn) unknown (AVES, 2011)
Aim: This study aims to evaluate and compare the effects of fentanyl and tramadol, used in combination with midazolam in the sedation procedures in dentistry so as to alleviate anxiety and postoperative pain associated with surgical third molar extraction in scared patients. Materials and Methods: This prospective randomized double-blind, placebo-controlled study enrolled 60 ASA I-II patients who had horizontal third molar extraction operation indication with APAIS scores above 10 points. All the paients were firstly given 0.03 mg kg-1 bolus midazolam and then they were randomized into three groups as Group A, only midazolam, Group B midazolam - fentanyl (1 μg kg-1), Group C, midazolam - tramadol (1 mg kg-1) combinations, respectively. All vital signs and intraoperative phalanx sweat index (PSI) data were recorded. Patients were assessed as for postoperative pain, and adverse effects. Results: No difference was found in PSI scores between the groups. During postoperative pain assessments, VAS scores of patients in Group C were lower than the other two groups at the postoperative 1st hour (p<0.05). Time to the need of the first rescue analgesic in Groups A, B, C were reported as 3, 3.5, and 5 hours respectively, while the time interval was comparatively prolonged in Group C (p<0.01). Conclusion: Tramadol has observedly provided more effective analgesia in third molar surgery than fentanyl, and placebo.
Keywords: Anxiety; Conscious Sedation; Oral Surgery